Stopień dostosowania zakładów mleczarskich do wymagań unijnych w dniu akcesji Polski do Unii Europejskiej - Romaniuk, Krystyna; Szczubełek, Grzegorz (Level of Adjustment of Polish Dairy Plants to the European Quality Standards on the Day of Poland's Accession to the European Union, 2005)
Poland's accession to the European Union was connected with introducing certain changes to the quality standards at Polish dairy plants. This resulted from the need to adjust these standards to the regulations specified in Directive 92/46/EEC. This Directive is a legal act that must be strictly observed by all economic entities conducting business activity in the dairy sector. On the day of Poland's accession to the Union (May 1, 2004), 204 dairy plants were granted a permission to sell their products, according to Directive 92/46/EEC, and 144 dairy plants obtained a transitional period for necessary structural changes, which have to be introduced by the end of 2006.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 245-249